Globalization A Very Short Introduction - Steger, Manfred B. (Oxford; New York Oxford University Press, 2003)
This work offers a stimulating introduction to globalisation and its varying impacts across, between, and within societies. It is a readable book that contributes to a better understanding of the crucial aspects and dimensions of the developments and tr
Keywords: Globalization. POLITICAL SCIENCE -- Globalization. Internationalisatie